Nomophobia and smartphone addiction amidst COVID-19 home confinement: the parallel mediating role of digital gaming and social media tools usage across secondary school students - Aydin, Mehmet Kemal; Kuş, Metin (Frontiers in Psychology, 2023)
With the inevitable technological boom enforced by the COVID-19 lockdowns and online emergency remote teaching practices, the prevalence of nomophobia (NMP) and smartphone addiction (SA) among adolescents has become a pressing issue, which has become under scrutiny. However, the impact of social media tools usage (SMTU) and digital gaming behavior (DGB) on these phenomena remains unclear since there is little research focusing on the complex interplay among these variables. Regarding this context, the present study aimed to explore the parallel mediating role of secondary school students' SMTU and DGB in the relation between NMP and SA. In line with this aim, we employed a cross-sectional design with a critical case sampling strategy and collected data through an online survey from a total of 427 secondary school students in Istanbul in the 2021-2022 academic year. In order to test the parallel mediation model, we employed multiple linear regression models by utilizing PROCESS models with 5000 BC bootstrap samples and 95% CI. Results illustrated that there was an increase in the prevalence of NMP and SA during the COVID-19 home confinement as consistent with the previous research. The results also indicated that among the multiple mediators, the mediating role of SMTU was significant in the relation between NMP and SA. This means NMP has direct and indirect significant impact on SA through SMTU. However, the mediating role of DGB was found nonsignificant in this relationship. Our results are robust and hold key contributions to both theoria and praxis in educational psychology research realm by disentangling the complex underlying mechanism between NMP, SMTU, DGB, and SA. On the practical side, our results provide insightful implications for school boards and researchers in the development of effective interventions.